2021
DOI: 10.1002/adhm.202100619
|View full text |Cite
|
Sign up to set email alerts
|

The Action‐Networks of Nanosilver: Bridging the Gap between Material and Biology

Abstract: The emergence of nanosilver (silver in nanoscale shapes and their assemblies) benefits the landscape of modern healthcare; however, this brings about concerns over its safety issues associated with an ultrasmall size and high mobility. By reviewing previous reporting details about the synthesis and characterization of nanosilver and its biological responses, a gap between materials synthesis and their biomedical uses is characterized by the insufficient understanding of the interacting and interplaying nanosca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 248 publications
0
7
0
Order By: Relevance
“…However, applications of these surfaces in “ uninfected tissues ” to prevent DAIs should be careful and in strict guidance, because the prolonged release of prophylactic antibiotics possibly contributes to arising resistant mutants [ 115 ]. Silver-based surfaces also have attractive efficacy in the prevention of DAIs [ 116 ], improper use of this material may also pose bacterial-resistant problems [ 117 , 118 ]. In addition, pathogenic bacteria have many defensive actions resistant to antimicrobial challenges [ 91 , 119 , 120 ]: (a) express polymer biofilms to protect themselves from antibiotic attacks; (b) remodel their outer surface to reduce antibiotic uptake; (c) synthesize precursors to modify the target of antimicrobials; (d) produce enzymes to detoxify dangerous drugs.…”
Section: Clinical Features Of Device-associated Infectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, applications of these surfaces in “ uninfected tissues ” to prevent DAIs should be careful and in strict guidance, because the prolonged release of prophylactic antibiotics possibly contributes to arising resistant mutants [ 115 ]. Silver-based surfaces also have attractive efficacy in the prevention of DAIs [ 116 ], improper use of this material may also pose bacterial-resistant problems [ 117 , 118 ]. In addition, pathogenic bacteria have many defensive actions resistant to antimicrobial challenges [ 91 , 119 , 120 ]: (a) express polymer biofilms to protect themselves from antibiotic attacks; (b) remodel their outer surface to reduce antibiotic uptake; (c) synthesize precursors to modify the target of antimicrobials; (d) produce enzymes to detoxify dangerous drugs.…”
Section: Clinical Features Of Device-associated Infectionsmentioning
confidence: 99%
“…This evidence gave us a comprehensive understanding of the biological actions of various silver-, zinc-, and copper-based materials, which are extensively concerned with developing antibacterial surfaces for medical devices [ 116 , 265 ]. However, they are normally passive studies that just demonstrate the immune-interfering actions of synthetic antibacterial materials, rather than active studies directly taking advantage of immunomodulatory biomaterials to construct antibacterial activity.…”
Section: Innovative Designs To Mitigate Device-associated Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…osseointegration for bone implants) performances of the implants. 8,[10][11][12] It was demonstrated that the high sensitivity of biomaterials to infections is related to bacterial contamination and undesirable host responses that compromise the intrinsic immune capability in defence against bacterial colonization. 13,14 In this respect, antibacterial designs addressing the intrinsic immune responses of the human body to tissue injuries would be more promising.…”
mentioning
confidence: 99%
“…1–4 To reduce the infection risks, various surfaces directly targeting pathogenic microbes have been developed in terms of local release or/and direct contact actions of antibiotics, synthetic antimicrobial peptides, antibacterial metals/metal compounds (silver, copper, and zinc are the most common ones), etc. 5–9 Since mammalian and bacterial cells share many similar adhesive mechanisms, it is still a challenge to design multi-functional antimicrobial surfaces, i.e. simultaneously promoting the antibacterial efficacy and tissue-integration ( e.g.…”
mentioning
confidence: 99%